Synthesis of Ba0.6Sr0.4TiO3 nano powder through slow rate sol-gel route as a dielectric material - Ruthramurthy, Balachandaran; Ho, Ce Yi; Koay, Yen Wei; Yow, Ho Kwang; Tan, Kar Ban; Mohd Noor, Ahmad Fauzi; Srekantan, Srimala (IDOSI Publications, 2010)
Ba0.6Sr0.4TiO3 was prepared through slow rate sol-gel route, characterized and investigated to determine the suitability as a dielectric material in the capacitor of a DRAM cell. X-ray diffractometer results show that single phase formation occurred at 800°C. The crystalline size of Ba0.6Sr0.4TiO3 was found to be in the range of 74.21 nm to 98.76 nm. Scanning electron microscopy analysis shows that the particles are spherical in nature and in the sample calcined at 800°C do not agglomerate. The dielectric constant range ranges from 408 to 1042 and the dielectric loss ranges (measured at 1 kHz) from 0.065 to 0.232.